A Curricular Study of Promoting Student Creativity and Agency through Classical Literature Classes Based on the Works of Kim Soo-young - Lee, Hyeon-Jeong (International Journal of Korean Humanities and Social Sciences, 2024)
This paper analyzes a real classroom curriculum using classical literature in a second-year Classical Literature classroom at a high school in Seoul, South Korea. The class was designed in a very creative way. Learners who signed up for this class could freely choose an author. Among them, Kim Soo-young (김수영) was the most voted for author. The class was organized in teams where learners participate through team activities. The teams read and interpreted Kim's poetry and prose. Each student then spoke about their favorite piece. The teams discussed their favorite pieces, then decided which work represents the team. One of the team members introduced the selected work to the other students. The students then organized a performance of the work presented with others in the class. After some discussion, Kim’s poetry, prose, and diary entries are reimagined in the form of a play. Team members share and prepare a performance of the play they have discussed. Students were able to practice as playwrights, directors, prop designers, and sound effect engineers. After this preparation, all five teams performed their plays. Using the work of Kim Soo-young, students were able to interpret literature into their own creative works. This curriculum asked students to create as well as evaluate other performances, allowing them to practice self-directed learning and develop agency over their study of classical literature. This lesson also allowed students to foster creativity through collaboration and discussion with their peers, practicing key social skills such as empathy and consideration for others.